2022
DOI: 10.1101/2022.04.20.488937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supercoiling-mediated feedback rapidly couples and tunes transcription

Abstract: Transcription induces a wave of DNA supercoiling, altering the binding affinity of RNA polymerases and reshaping the biochemical landscape of gene regulation. As supercoiling rapidly diffuses, transcription dynamically reshapes the regulation of proximal genes, forming a complex feedback loop. The resulting intergene coupling may provide a mechanism to control transcriptional variance in engineered gene networks and explain the behavior of co-localized native circuits. However, a theoretical framework is neede… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We found that evolved genomes in the model are enriched in divergent pairs of always-active genes, as well as in convergent pairs that act as bistable toggle switches (Gardner et al, 2000; Johnstone and Galloway, 2022); the evolution of such systems substantiates the theoretical predictions made by models that explicitly describe the movement of RNA polymerases during gene transcription, such as Sevier and Hormoz (2021). Then, we showed that the local organization of the genome into convergent or divergent pairs of genes is not sufficient to explain the transcriptional response of individuals to different environments, but that larger subnetworks can be required to selectively inhibit genes in specific environments.…”
Section: Discussion and Perspectivesmentioning
confidence: 97%
See 2 more Smart Citations
“…We found that evolved genomes in the model are enriched in divergent pairs of always-active genes, as well as in convergent pairs that act as bistable toggle switches (Gardner et al, 2000; Johnstone and Galloway, 2022); the evolution of such systems substantiates the theoretical predictions made by models that explicitly describe the movement of RNA polymerases during gene transcription, such as Sevier and Hormoz (2021). Then, we showed that the local organization of the genome into convergent or divergent pairs of genes is not sufficient to explain the transcriptional response of individuals to different environments, but that larger subnetworks can be required to selectively inhibit genes in specific environments.…”
Section: Discussion and Perspectivesmentioning
confidence: 97%
“…Moreover, integrating a model of gene regulation by DNA supercoiling into a more comprehensive evolutionary model of the genome that allows for classical gene regulation via transcription factors, such as the model presented in Crombach and Hogeweg (2008), would help shed light on the coevolution between the different modes of gene regulation that are available to bacterial genomes. Finally, from an experimental perspective, a better understanding of the regulatory interactions caused by the transcription-supercoiling coupling could help design more reliable synthetic genetic constructs, as explored in Johnstone and Galloway (2022).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation